Myeloid-derived suppressor cells in gliomas - Gieryng, Anna; Kaminska, Bozena (Contemporary Oncology/Współczesna Onkologia, 2016)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of early myeloid progenitors and precursors at different stages of differentiation into granulocytes, macrophages, and dendritic cells. Blockade of their differentiation into mature myeloid cells in cancer results in an expansion of this population. High-grade gliomas are the most common malignant tumours of the central nervous system (CNS), with a poor prognosis despite intensive radiation and chemotherapy. Histopathological and flow cytometry analyses of human and rodent experimental gliomas revealed the extensive heterogeneity of immune cells infiltrating gliomas and their microenvironment. Immune cell infiltrates consist of: resident (microglia) and peripheral macrophages, granulocytes, myeloid-derived suppressor cells, and T lymphocytes. Intratumoural density of glioma-associated MDSCs correlates positively with the histological grade of gliomas and patient’s survival. MDSCs have the ability to attract T regulatory lymphocytes to the tumour, but block the activation of tumour-reactive CD4+ T helper cells and cytotoxic CD8+ T cells. Immunomodulatory mechanisms employed by malignant gliomas pose an appalling challenge to brain tumour immunotherapy. In this mini-review we describe phenotypic and functional characteristics of MDSCs in humans and rodents, and their occurrence and potential roles in glioma progression. While understanding the complexity of immune cell interactions in the glioma microenvironment is far from being accomplished, there is significant progress that may lead to the development of immunotherapy for gliomas.